Avaliação da migração de nifas de Scaptocoris carvalhoi Becker, 1967 (Hemiptera, Cydnidae) em plantas de importância econômica e invasora em teste com oportunidade de escolha - Medeiros, Mauro Osvaldo [UNESP]; Costa, Ciniro [UNESP]; Amaral, José Libério do [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP] (My University, 2015)
One of the factors that affect the control of brown - roots environmental bedbug is the wide availability of plant species. Thus, this study aimed to evaluate the migration of nymphs of the brown - roots between plant species of economic importance and invasive stinkbug. Eight species of plants have been established in a set formed by eight circular PVC containers, connected symmetrically with free communication to a central circular container. The experiment was arranged in a completely randomized design and consisted of eight treatments and six replications. The test evaluations were performed on 15o , 30o , 45o and 60o days after the release of the nymphs, by counting the insects that migrated to the roots of different plants. It was observed that by the 30o day of early release nymphs, no significant differences (P < 0,05) in the choices nymph by plants. B. alata at 15 days of initial release and B. alata and grass-dictyoneura at 30 days were plants that had higher migration. All counts were carried out on 45o and 60o days, the migration of U. brizantha cv. Marandu presented significantly higher than all other species tested plants nymphs.

Um dos fatores que afetam o controle do percevejo castanho-das-raízes no ambiente é a grande disponibilidade de espécies de plantas. Desta forma, este trabalho teve como objetivo avaliar a migração das ninfas do percevejo castanhodas-raízes em espécies de plantas de importância econômicas e invasoras. Oito espécies de plantas foram estabelecidas, em um conjunto formado por oito recipientes circulares de PVC, interligados simetricamente com livre comunicação a um recipiente central circular. O experimento foi organizado segundo o delineamento inteiramente casualizado e constou de oito tratamentos e seis repetições. As avaliações do ensaio foram realizadas nos 15o , 30o , 45o e 60o dias após a liberação das ninfas, por meio da contagem de insetos que migraram para as raízes das diferentes plantas. Observou-se que até o 30o dia do início da liberação das ninfas, não houve diferenças significativas (P<0,05) nas escolhas da ninfa pelas plantas. A B. alata aos 15 dias da liberação inicial e B. alata e capim-dictyoneura aos 30 dias foram as plantas que apresentaram maior migração. Nas contagens realizadas no 45o e 60o dia, a U. brizantha cv. Marandu apresentou migração de ninfas significativamente maior que todas as demais espécies de plantas testadas.
Evaluation of migration nymphs scaptocoris carvalhoi becker, 1967 (hemiptera, cydnidae) between economic importance of plants and invasive testing with opportunity to choose
Keywords: Migration; Invading plant; Pasture; Behavior; Insect soil; Migração; Planta invasora; Pastagem; Comportamento; Inseto de solo